2019
DOI: 10.1016/j.celrep.2019.10.065
|View full text |Cite
|
Sign up to set email alerts
|

The X-Linked Intellectual Disability Gene Zdhhc9 Is Essential for Dendrite Outgrowth and Inhibitory Synapse Formation

Abstract: Graphical Abstract Highlights d Palmitoylation of Ras by Zdhhc9 regulates dendritic growth d Palmitoylation of TC10 by Zdhhc9 regulates inhibitory synapse formation d Loss of Zdhhc9 impairs excitatory/inhibitory synapse balance d Zdhhc9 knockout mice exhibit increased seizure activity and network excitability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 131 publications
(136 reference statements)
4
90
0
Order By: Relevance
“…Of these, five—including MYRF, Otud7b, Zdhhc9, Efnb3 , and Nudt4 —were indeed found to be upregulated in miR‐145‐5p knockdown OPCs (Figure 6c). Aside from MYRF, none of the additionally identified targets have known roles in OL differentiation or myelin formation—though Otud7b, Zdhhc9 , and Efnb3 have been characterized to some degree in neurons (Cui et al, 2018; Henderson et al, 2019; Shimell et al, 2019). This certainly does not preclude them from having undiscovered roles in OLs; however, expression of all four were normalized concurrent with MYRF knockdown in anti‐145 OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, five—including MYRF, Otud7b, Zdhhc9, Efnb3 , and Nudt4 —were indeed found to be upregulated in miR‐145‐5p knockdown OPCs (Figure 6c). Aside from MYRF, none of the additionally identified targets have known roles in OL differentiation or myelin formation—though Otud7b, Zdhhc9 , and Efnb3 have been characterized to some degree in neurons (Cui et al, 2018; Henderson et al, 2019; Shimell et al, 2019). This certainly does not preclude them from having undiscovered roles in OLs; however, expression of all four were normalized concurrent with MYRF knockdown in anti‐145 OPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function variants in the Golgi-localized ZDHHC9 are linked to X-linked intellectual disability (XLID) (Han et al, 2017;Masurel-Paulet et al, 2014;Mitchell et al, 2014;Raymond et al, 2007;Tzschach et al, 2015), sometimes with an increased incidence of epilepsy (Baker et al, 2015). zDHHC9 regulates of dendritic growth and inhibitory synapse formation through the palmitoylation of the two GTPases, Ras and TC10, with significant implications for maintaining excitatory/inhibitory (E/I) balance in the brain (Shimell et al, 2019). Zdhhc9-knockout mice have altered E/I balance and exhibit seizure-like activity, which could contribute to XLID etiology.…”
Section: Pat Localization In Health and Diseasementioning
confidence: 99%
“…Zdhhc9-knockout mice have altered E/I balance and exhibit seizure-like activity, which could contribute to XLID etiology. (Shimell et al, 2019). Genome-wide association studies have found deletions in the region of chromosome 11 that encodes ZDHHC5 in patients with bipolar disorder and schizophrenia (Fallin et al, 2004; Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014).…”
Section: Pat Localization In Health and Diseasementioning
confidence: 99%
“…To determine whether Zdhhc5 is involved in dendritic arborization and/or the formation of excitatory and inhibitory synapses, hippocampal neurons were transfected with eGFP plus the indicated constructs and immunostained for PSD-95 and gephyrin (faithful markers of excitatory and inhibitory synapses, respectively (Brigidi et al, 2015;Shah et al, 2019;Shimell et al, 2019); masking shown in Supplementary Figure 1A, B). While Zdhhc5 knockdown did not impact dendritic length ( Figure 1A), complexity ( Figure 1B Figure 1B for the creation of masks to quantify synaptic marker density).…”
Section: Zdhhc5 Promotes Excitatory Synapse Formation and Regulates Smentioning
confidence: 99%
“…Biotinylation experiments were performed as previously described (Shimell et al, 2019). Briefly, neurons in 10cm dishes were nucleofected with indicated constructs and experiments were carried out at 13 DIV.…”
Section: Biotinylation Assaymentioning
confidence: 99%